Peran ulu al-albab dalam al-Amr bi al-Ma’ruf wa al-Nahy ‘an al-Munkar menurut Al-Qur’an - Mira Fauziah (TAFSE: Journal of Qur'anic Studies, 2018)
Ulu al-albab is basically a human being who is able to catch and take lessons from the signs of Allah's greatness and feel His presence. In the Indonesian vocabulary, this understanding has the same meaning as an intelligent person, usually used with the term intellectual or intellectual. From the explanation of the verses of the Qur'an, it can be seen that the ulu al-albab is a human being who has received Allah's guidance. As a chosen human being, ulu al-albab certainly has higher religious and moral responsibilities than ordinary humans. The responsibilities in question include the obligation to uphold al-amr bi al-ma'ruf wa al-nahy 'an al-munkar as a whole among mankind.Ulu al-albab pada dasarnya adalah manusia yang mampu menangkap dan mengambil pelajaran dari tanda-tanda kebesaran Allah serta merasakan keberadaan-Nya. Dalam perbendaharaan Bahasa Indonesia, pengertian ini sama maknanya dengan orang yang berakal biasa digunakan dengan istilah intelektual atau cendikiawan. Dari penjelasan ayat-ayat al-Qur’an, terlihat bahwa ulu al-albab merupakan manusia yang telah memperoleh hidayah Allah. Sebagai manusia pilihan, ulu al-albab tentu mempunyai tanggung jawab agama dan moral yang lebih tinggi dibandingkan dengan manusia biasa. Tanggung jawab yang dimaksud di antaranya kewajiban menegakkan al-amr bi al-ma’ruf wa al-nahy ‘an al-munkar secara menyeluruh di kalangan umat manusia.